Sinergi Keluarga dan Sekolah: Studi tentang Partisipasi Orang Tua dalam Mendukung Keberhasilan Pendidikan Anak di SMA Katolik St. Ignatius Manado - Heatubun, Antonius (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2024)
This study examines the synergy between family and school at St. Ignatius Catholic High School in Manado, focusing on parental participation in supporting children's educational success. A qualitative approach is used to understand the dynamics of interaction between parents and the school in both academic and character development aspects of students. The findings reveal that this synergy is created through open communication between teachers and parents, as well as the active involvement of parents in various school activities, such as family mass and non-academic events. Factors such as parents' awareness of the importance of their role, their busy schedules, and economic conditions influence their participation. The established synergy positively impacts not only students' academic achievements but also their character development. The presence of supportive parents at home and schools that provide the right facilitation helps students feel more confident and motivated. This study emphasizes that collaboration between family and school is essential for the educational success of students.